Między ciszą a ciszą słowa się kołyszą - polski język migowy (PJM) jako element identyfikacji społecznej Głuchych = Between stillness and stillness words are swaying - polish sign language (PSL) as an element of the social identity of Deaf - Walas, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article is an attempt to bring readers closer to the Deaf Community and the Polish Sign Language (PJM) as an element of the cultural identity of the Deaf Community. The text attempts to introduce the history of the Polish Sign Language and point to its elements as the natural language of Deaf people (including manual and non-manual components, visual and spatial grammar). An important element of the article is a reference to legal acts concerning the use of sign language in education of the Deaf. The text also aims to highlight the problems in communication for Deaf people in public institutions, e.g. government offices, hospitals.
Keywords: Wspólnota Głuchych; Kultura Głuchych; polski język migowy (PJM); system językowo-migowy (SJM); gramatyka wizualnoprzestrzenna; edukacja; audyzm; Community of Deaf; Culture of Deaf; Polish Sign Language (PSL); Signed Polish; spatio-visual grammar; audism; education